The role of pneumoperitoneum in the glomerular filtration in an experimental model with 2/3 reduction of the renal mass (Acta Scientiarum. Health Sciences, 2017)
Objective: To evaluate the influence of the CO2 pneumoperitoneum in the glomerular filtration in a rat model with a 2/3 reduction of renal parenchyma. Methods: Adult Wistar male rats (n = 50) were subjected to right nephrectomy and a 2/3 ligature of the renal left vascular branch. Animals were randomly distributed as follows: GI (n = 10) - simulated, GII (n = 20) –8 mm Hg pneumoperitoneum, and GIII (n = 20) –15 mm Hg pneumoperitoneum. After two (GIIA and GIIIA) and three (GIIB and GIIIB) hours of insufflation, and one hour of disinsufflation, they were evaluated for the following aspects: mean blood pressure (MBP), microhematocrit, urinary volume and inulin clearance. Results: The microscopic aspects showed signs of glomerulosclerosis that caused proteinuria. Renal function with8 mm Hg pneumoperitoneum after two hours of disinsufflation (Î”% = 202.68) was better than after three hours (Î”% = 10.89). With15 mm Hg pneumoperitoneum, the renal function was damaged by both procedures, that is, two (Î”% = -3.57) and three hours (Î”% = -3.25). Conclusion: Inulin clearance evidenced renal insufficiency in the model with a 2/3 reduction of renal mass, and depending on both the increase of the exposure time and the pressure intensity, it can be more intensified.